Romanian Journal of Indian Studies No. 5 2021 - GLIGOR, Mihaela (2021)
India is a mixture of emotions, colours, feelings, music, happiness,sorrow, life and death, gods and people. India is an endless puzzlewhich each soul that meets its mystery tries to solve. India is infinite,just as untrammelled as the fascination that it produces in the others.India is an incredible rich culture, with a history of thousands ofyears. It saw the rise of various civilizations, religions, dynasties, humangroups, cultures and arts. India has been presented and represented inmany forms in literary discourses, arts and heritage symbols. But thecountry is so vast that there always remains an area to be explored.Moreover, there are many new things to be interpreted. Any discussion onanything belonging to India and its culture is incomplete withoutinterdisciplinary dialogue between various cultural aspects and elements.